1965
DOI: 10.1530/jrf.0.0100189
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Ectopic Implantation of Eggs and Early Embryos in Guinea-Pigs

Abstract: Successful primary abdominal implantation and development has been induced in the guinea-pig by transection of the oviducts 1 to 3 days after mating although attempts made to induce tubal implantation by ligature of the utero-tubal junction failed.Development also took place in four out of eighteen pre-implantation eggs (aged 4 to 5 days post coitum) transplanted into the kidney or abdominal muscle. In six cases, where post-implantation conceptuses (aged 9\ m=1/ 2\ and 12 days post coitum) were transplanted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Cases of secondary abdominal pregnancy have been reported in several animal species, and they have been experimentally induced in rabbits, guinea pigs (Bland & Donovan 1965), rats (Bunte & Hildebrandt 1975) and mice (Hreshchyshyn & Hreshchyshyn 1964). In humans, secondary abdominal pregnancy is usually subsequent to tubal pregnancies with a rupture of the oviduct (Smith et al 1974).…”
Section: Abdominal Pregnanciesmentioning
confidence: 99%
“…Cases of secondary abdominal pregnancy have been reported in several animal species, and they have been experimentally induced in rabbits, guinea pigs (Bland & Donovan 1965), rats (Bunte & Hildebrandt 1975) and mice (Hreshchyshyn & Hreshchyshyn 1964). In humans, secondary abdominal pregnancy is usually subsequent to tubal pregnancies with a rupture of the oviduct (Smith et al 1974).…”
Section: Abdominal Pregnanciesmentioning
confidence: 99%
“…On the other hand, Bland and Donovan [17] were able to induce abdominal implantation in guinea pig by introducing fertilized eggs into the peritoneal cavity. These authors found that trophoblast was produced in all cases, but the nontrophoblastic component of these implants was restricted to a mesenchyme-like tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies, in which blastocysts were restricted to the oviduct, all noted that they remained free within the lumen [11,[15][16][17][18], It was thought that implantation required exposure of the blastocyst to a uterine factor which was believed to initiate nidation by increasing the adhesiveness of the blastocyst through loss of the zona pcllucida [22]. Bron son and Cunnane [21], however, reported that blastocysts obtained from the uteri of donor mice on day 3.5 of pregnancy failed to implant when transferred to the oviducts of pseudopregnant mice.…”
Section: Discussionmentioning
confidence: 99%
“…To date, all attempts to produce tubal implantations by restricting the embryo to the oviduct, ligating the uterotubal junction [11,[14][15][16][17][18][19], administering exogenous estro gen [20], or transferring blastocysts to recipi ent oviducts [21] have failed. Bronson and Cunnane [21] investigated the possible effect of prior exposure of the blastocyst to the uter ine environment on tubal implantations.…”
Section: Introductionmentioning
confidence: 99%